Effects of Recreational Ski Mountaineering on Cumulative Muscle Fatigue – A Longitudinal Trial - Haslinger, Simon; Blank, Cornelia; Morawetz, David; Koller, Arnold; Dünnwald, Tobias; Berger, Sarah; Schlickum, Nico; Schobersberger, Wolfgang (Frontiers in Physiology, 2018)
Sport is known to have many positive effects on mental and physical health. High-intensity exercise is considered to decrease muscle strength and induce muscle fatigue, which is associated with a higher risk of injury. In recreational alpine skiers, a decrease of eccentric peak hamstring torque, as an indication of muscle fatigue, occurs even after 1 day of skiing. The popularity of ski mountaineering is increasing enormously, but no studies are available on its effects on muscle strength. Therefore, the present study examined the consequences of ski mountaineering on muscle fatigue of the concentric/eccentric quadriceps and/or hamstrings. In addition, a possible role of myofascial foam rolling in reducing muscle fatigue was evaluated. Fifty recreational ski mountaineers (27 males, 23 females) completed five consecutive tours of ski mountaineering within 1 week. After each day of skiing, participants underwent an isokinetic muscle test assessing the concentric and eccentric muscle strength of both thighs. One group completed an additional session of myofascial foam rolling. Right and left concentric quadriceps peak torque, left hamstrings peak torque, left eccentric quadriceps peak torque, as well as right and left hamstring peak torque, were reduced after a single day of ski mountaineering (p0.016 for all). However, no cumulative muscle fatigue was detected and we could not demonstrate any effect of myofascial foam rolling. The results show conclusively that a single day of ski mountaineering leads to a significant decrease of concentric and eccentric quadriceps and hamstring strength. Therefore, in order to improve muscle strength for the ski mountaineering season, a physical training program including concentric and eccentric methods can be recommended.